PENDAMPINGAN PEMBELAJARAN TARKIB PEGON DENGAN METODE BERNYANYI PADA MURID DI MUSHOLLA RIYADUS SHOLIHIN UMBULSARI JEMBER - Nafsah, Nor Holis bin; Khoiroh, Immatul; Nafisah, Iffatun (INAIFAS Press, 2025)
The use of an effective method in the learning process is a must in order to achieve learning targets. The purpose of this study is to describe the implementation of Pegon Tarkib Learning Assistance with the Singing Method for students at the Riyadus Sholihin Mundurejo Umbulsari Jember Mosque. The method used in this study is a qualitative method. and This study focuses on introducing, memorizing, and understanding Pegon Tarkib to students by using the singing method. And after going through an in-depth research process during the mentoring, in this research the researcher concluded that after undergoing intensive training using the singing method, the 10 students aged 9 years and above had made progress in recognizing, reading and memorizing Pegon Tarkib.